PERSEPSI KONSUMEN TENTANG INFUSED COFFEE DI TITIK KUMPUL COFFEE BREWERS KOTA BATAM - Lubis, Taufik Bachrul Ulum; Lapotulo, Nensi; Pratama, Tito; Dailami, Dailami (Bussman Journal : Indonesian Journal of Business and Management, 2025)
This study aims to explore consumer perceptions of infused coffee products offered by Titik Kumpul Coffee Brewers in Batam City. Using a qualitative approach and case study method, this study examines how consumers assess the aspects of taste, appearance, health benefits, and innovation value of infused coffee. The results show that positive consumer perceptions are formed through the multisensory experience provided by the product, the shop atmosphere that supports the third-place concept, and a strong product narrative. These findings provide important implications for experiential marketing strategies and product innovation in the local coffee industry